Characteristics of Moderate Da'wah in The View of Abdul Mun'im - Edlyn, M. Keanu Zimran; Apriliani, Yola; Fuada, Nadiya; Bono, Shafa Ajeng Prameswari; Sari, Hilda Rara (International Tatho Academics, 2024)
The purpose of this study is to identify the characteristics of moderate Islamic da'wah in the view of H. Abdul Mun'im. This qualitative study uses an analytical-narrative approach. The values of wasathiyah Islamic teachings become the theory of analysis of the subject matter of the study. Research data were obtained through observation techniques on Youtbue content about Ustadz H. Abdul Mun'im's da'wah entitled